Yahweh fighting from heaven : God as warrior and as God of heaven in the Hebrew Psalter and ancient Near Eastern iconography - Klingbeil, Martin Gerhard (Stellenbosch : Stellenbosch University, 2012)
Thesis (DLitt)--Stellenbosch University, 1995.